2020
DOI: 10.1016/j.drup.2020.100733
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 update: The race to therapeutic development

Abstract: The COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), represents an unprecedented challenge to global public health. At the time of this review, COVID-19 has been diagnosed in over 40 million cases and associated with 1.1 million deaths worldwide. Current management strategies for COVID-19 are largely supportive, and while there are more than 2000 interventional clinical trials registered with the U.S. National Library of Medicine (clinicaltrials.gov), results that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 86 publications
0
62
0
Order By: Relevance
“…Presently, SARS-CoV-2 infection therapy includes immunomodulatory drugs, plasma from individuals recovered from COVID-19, and several pharmacological treatments [ 81 ]. In this regard, despite numerous repurposed drugs being tested, only the nucleoside analog remdesivir has been officially approved by the American Food and Drug Administration (FDA) agency to date [ 82 ].…”
Section: Prophylaxis and Therapy Of Hcov Diseasesmentioning
confidence: 99%
“…Presently, SARS-CoV-2 infection therapy includes immunomodulatory drugs, plasma from individuals recovered from COVID-19, and several pharmacological treatments [ 81 ]. In this regard, despite numerous repurposed drugs being tested, only the nucleoside analog remdesivir has been officially approved by the American Food and Drug Administration (FDA) agency to date [ 82 ].…”
Section: Prophylaxis and Therapy Of Hcov Diseasesmentioning
confidence: 99%
“…Effective pharmacological interventions are therefore urgently needed. Since the first report of COVID-19 in late 2019, relevant progress has been achieved in drug discovery and development within a remarkable timeline [ [7] , [8] , [9] , [10] , [11] ]. Several vaccines and drugs are undergoing clinical trials, but research on novel antivirals remains important.…”
Section: Introductionmentioning
confidence: 99%
“…Caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), Coronavirus Disease 2019 (COVID-19) pandemic has continued to spread around the world and led to a global health emergency of inconceivable magnitude. 1,2 Currently, vaccines, including Pfizer-BioNTech COVID-19 vaccine and Moderna's COVID-19 vaccine, are authorized for emergency use to prevent COVID-19. 3 Previous study indicated that use of a vaccine in combination with measures which could reduce contact between susceptible individuals and COVID-19 carriers will significantly decrease the per-day risk of infection so long as at least 50% of people receive it.…”
Section: Dear Editormentioning
confidence: 99%